Evaluasi Jalur Akses Pemadam Kebakaran Pada Proyek Pembangunan Research & Technology Center Pertamina - Joko Susilo; M. Alif Anugrah; Rizky Fathan Witjaksono; Mohamad Haifan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The Pertamina Research & Technology Centre Facility is a laboratory building designed to support research activities, where laboratory space is a critical element in the design of a research and laboratory centre. Due to activities involving chemicals, crude oil and other products, the risk of chemical and biological contamination, radiation exposure, explosions and fires is higher than in most other facilities. This potential hazard requires a well-designed building access system to prevent the risk of fire and explosion. The aim of this study is to evaluate whether the building access for fire and explosion protection in this facility is adequate and meets established standards. The evaluation method used is a qualitative approach through a literature review on the principles of fire access in buildings, which is then applied to the Pertamina Research & Technology Center facility located at Jl. Daan Mogot Km. 16, West Jakarta. The results of the evaluation indicate that the fire egress in this facility meets the established standards, allowing the occupants to conduct research activities more safely against potential fire and explosion hazards in the future.